Sugar cookie murder eaudiobook - Fluke, Joanne (Hannah Swensen Mystery, 2004)
The holidays are the icing on the cake for bakery owner Hannah Swensen. Surrounded by her loved ones, she has all the ingredients for a perfect Christmas—until murder is added to the mix ... When it comes to holidays, Minnesotans rise to the occasion—and the little town of Lake Eden is baking up a storm with Hannah leading the way. The annual Christmas Buffet is the final test of the recipes Hannah has collected for the Lake Eden Holiday Buffet Cookbook. The recently divorced Martin Dubinski arrives at the buffet with his new Vegas showgirl wife—all wrapped up in glitter and fur. His ex-wife, however, seems as cool as chilled eggnog. And when Hannah's mother's antique Christmas cake knife disappears, its discovery in the décolletage of the new—and now late—Mrs. Dubinski puts the festivities on ice. With everyone stranded at the community center by a blizzard, Hannah puts her investigative skills to the test, using the ingredients at hand: half the town of Lake Eden—and a killer. Now, as the snowdrifts get higher, it's up to Hannah to dig out all the clues—and make sure that this white Christmas doesn't bring any more deadly tidings ... "Wacky and delightful characters, plus tempting recipes from appetizers to desserts, make this lighthearted offering sure to please the palate of any cozy fan."—Publishers Weekly "Fluke's talent for spinning a mesmerizing tale carries on in this sixth book, and its holiday recipes are an added treat for readers."—Times News RecordIncludes over fifty original recipes for you to try!